Over 50 years of trial in Acta Psychiatrica Scandinavica: a survey - Al Marhi Muhammad O; Almerie Muhammad Q; Matar Hosam E; Adams Clive E (Trials, 2009)
Abstract Background Randomised controlled trials are the gold standard for evaluating mental health care interventions. We assessed the content and quality of trials published in Acta Psychiatrica Scandinavica and Supplementum since 1948. Methods All trials were identified manually, quality assessed, data extracted, and sought on Medline. Results About 8.6% of all reports in the journal were clinical trials (n = 582) with the peak frequency in the 1980s. Most originate from Europe (80%) and focus on depression (~38%) or schizophrenia (27%). The median sample size is 44. We found only two trials that fully met the criteria of quality reporting RCTs set by CONSORT statements (0.34%) since 1996. Less than 50% of records were possible to identify by a Medline search using broad methodological terms. Conclusion Acta is a major source of health trials. The standard of reporting is similar to other journals but better adherence to CONSORT would ensure higher quality of reports and better dissemination.